The professional personnel of the Silliman University Library System, 1950-1966 a study - Bañas, Eliseo P. (1974)
This study set out to accomplish the following: (1) to discover the initial personal characteristics that Silliman University Library personnel bring to their jobs; (2) to discover the initial academic characteristics of the same group; (3) to ascertain, through statistical approaches, the relationships between these initial characteristics and their overall performance while on the job; and, (4) to determine the relationships between the same initial characteristics and their length of service with the library system